SOME FURTHER LINGUISTIC ASPECTS OF THE CHESTER BEATTY PAPYRUS OF THE GOSPELS - Tarelli, C. C. (The journal of theological studies, 1942)
C. C. TARELLI; SOME FURTHER LINGUISTIC ASPECTS OF THE CHESTER BEATTY PAPYRUS OF THE GOSPELS, The Journal of Theological Studies, Volume os-XLIII, Issue 169-170,